2016
DOI: 10.1016/j.commatsci.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

On the crystalline structure of orthorhombic SrRuO3: A benchmark study of DFT functionals

Abstract: By investigating the crystalline structure of ground-state orthorhombic SrRuO 3 , we present a benchmark study of some of the most popular density functional theory (DFT) approaches from the local density approximation (LDA), generalized-gradient approximation (GGA), and hybrid functional families. Recent experimental success in stabilizing tetragonal and monoclinic phases of SrRuO 3 at room temperature sheds a new light on the ability to accurately describe geometry of this material by applying first-principl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…A somewhat different behaviour of the SOGGA functional in comparison to those of PBEsol and WC at 20% of HF exchange allows the decrease of MARE 2 to 0.59% showing that the range of a = 0.15-0.2 seems to be the most appropriate choice for the tilting and rotation angles. This observation is perfectly consistent with the result of mB1WC [4] -a combination of WC exchange, PBE correlation, and 16% of HF mixing -which is a bit lower (0.84%) compared to the MARE 2 value of WC at 15% of HF exchange (0.95%). But amounts of E X HF larger than 20% should not lead to a further improvement though, at least for PBEsol and WC approximations.…”
Section: Benchmark Of Hybrid Schemesupporting
confidence: 90%
See 2 more Smart Citations
“…A somewhat different behaviour of the SOGGA functional in comparison to those of PBEsol and WC at 20% of HF exchange allows the decrease of MARE 2 to 0.59% showing that the range of a = 0.15-0.2 seems to be the most appropriate choice for the tilting and rotation angles. This observation is perfectly consistent with the result of mB1WC [4] -a combination of WC exchange, PBE correlation, and 16% of HF mixing -which is a bit lower (0.84%) compared to the MARE 2 value of WC at 15% of HF exchange (0.95%). But amounts of E X HF larger than 20% should not lead to a further improvement though, at least for PBEsol and WC approximations.…”
Section: Benchmark Of Hybrid Schemesupporting
confidence: 90%
“…2 (b) where tilting and rotation angles of RuO 6 octahedra are taken into account. One can note that here at least ∼ 15% of HF mixing is necessary for WC and slightly less for PBEsol and SOGGA in order to get below a so-called satisfactory threshold of MAREs set to 1% in our previous paper [4]. The higher MARE 2 values compared to the errors of lattice constants and volume may be explained by the fact that variations in tilting and rotation angles involve very subtle energy changes which are much more harder to deal with.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We have chosen the PBEsol exchangecorrelation functional for the calculations because of its good performance in describing the crystalline structure of SrRuO 3 . 21 Besides, among revised generalized-gradient approximations for solids, this functional seems to be a more common choice for the plane-wave calculations with open-source pseudopotential libraries, making it easier to reproduce our findings. In general, we believe that the bulk-like nature of our modeling should not be an obstacle to realistically simulate thin-film behavior, since the thickness of the considered SrRuO 3 structure, ranging from 20 to 30 nm, 4 is far from the ultrathin limit.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…On the whole, precise identification of the tilt system is a very important point of any thin-film investigation because it was experimentally shown that physical properties of strained SrRuO 3 vary according to the octahedral rotation pattern. 11,13,14 Therefore, by having at our disposal reliable tools for ab initio modeling, thoroughly discussed in a previous paper, 21 we are willing to give a broader perspective on the crystalline as well as electronic structure of tensile strained SrRuO 3 .…”
Section: ■ Introductionmentioning
confidence: 99%